THE IMPACT OF FINTECH ON FINANCIAL INCLUSION FOR LOW-INCOME COMMUNITIES - Samudra Syarif Wahyu Hidayatullah; Saepullah; Kasmin; Frandy Putra Perdamen Tarigan (CV. Adiba Aisha Amira, 2025)
Financial inclusion is a critical factor in economic development, particularly for low- income communities that face barriers to accessing traditional financial services. The emergence of financial technology (fintech) has provided innovative solutions to enhance financial inclusion by leveraging digital platforms, mobile banking, and alternative credit scoring models. This study examines the impact of fintech on financial inclusion for low-income communities, utilizing a mixed-method research approach. Quantitative data from financial institutions and surveys are analyzed using statistical techniques to measure improvements in financial access, while qualitative insights from interviews with fintech users provide a deeper understanding of challenges and opportunities. The findings indicate that fintech has significantly increased access to financial services through mobile banking and digital payment solutions, enabling individuals without traditional bank accounts to conduct transactions, save money, and obtain credit. Additionally, fintech-driven innovations in microcredit and digital lending have expanded financial access for individuals lacking credit history or collateral. Fintech has also contributed to reducing transaction costs and improving efficiency, particularly in remittance services, thereby enhancing the financial stability of low-income households. However, challenges such as low digital literacy, cybersecurity risks, and regulatory concerns remain prevalent. Addressing these challenges requires collaborative efforts from governments, fintech providers, and financial institutions to develop policies that balance innovation with consumer protection. In conclusion, fintech plays a transformative role in promoting financial inclusion and economic empowerment for underserved populations. While fintech offers significant opportunities, ensuring its sustainable and equitable implementation necessitates improved financial literacy, robust security measures, and well-structured regulatory frameworks.